1999
DOI: 10.1557/s109257830000329x
|View full text |Cite
|
Sign up to set email alerts
|

CRYSTAL STRUCTURE AND DEFECTS IN NITROGEN-DEFICIENT GaN

Abstract: We have studied crystal structure and associated defects in GaN films grown on sapphire under nitrogen-deficient conditions by metalorganic chemical vapor deposition (MOCVD) and pulsed laser deposition (PLD). The structural quality of the PLD films grown at 750 0 C was comparable with those grown by MOCVD at 1050 0 C having threading dislocations density of about 10 10 cm -2 at a film thickness 150-200 nm. Microstructure of the PLD films grown at temperatures above 780 0 C was found to be similar to that of ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The electron diffraction patterns of the crystallites exhibited streaking of the diffraction spots perpendicular to the close-packed planes; also consistent with a structure containing numerous defects such as stacking faults. While these striations could also be described as micro-twinning, 38 the electron diffraction data and the presence of peaks attributable to both the cubic and hexagonal phases in the X-ray diffraction pattern suggest a disordered structure containing stacking faults.…”
Section: Discussionmentioning
confidence: 99%
“…The electron diffraction patterns of the crystallites exhibited streaking of the diffraction spots perpendicular to the close-packed planes; also consistent with a structure containing numerous defects such as stacking faults. While these striations could also be described as micro-twinning, 38 the electron diffraction data and the presence of peaks attributable to both the cubic and hexagonal phases in the X-ray diffraction pattern suggest a disordered structure containing stacking faults.…”
Section: Discussionmentioning
confidence: 99%
“…However, we have shown that gallium oxynitride, prepared by ammonolysis of a nickel gallate precursor, has a complex structure, which could be considered as a polytype where two arrangements of cubic (zinc-blende) and hexagonal (wurtzite) structures may coexist [8,18]. The mixing of the two structures has been observed in GaN thin films [13][14][15][16] but, to our knowledge, such a result has not been reported elsewhere for gallium oxynitride powders. While the crystal structures of zinc-blende and wurtzite are very similar [12], their lattice vibrations are different.…”
Section: Introductionmentioning
confidence: 91%
“…GaN is known to be highly stable in the hexagonal wurtzite structure [12], but the growth of the cubic (zinc-blende) phase has also been reported in thin films [13][14][15][16]. Zincblende-wurtzite polytypism is well known in semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, Ga-terminated films would grow on the (001) plane of LiGaO 2 that has a cationterminated surface, 5 16 All the chemicals and solvents were purified and dried by standard methods described in the literature. 17 The 1 H and 13 C NMR spectra were recorded on a Bruker DPX 300 MHz spectrometer with chemical shifts referenced internally to benzene-d 6 . FTIR spectra were recorded on a Nicolet Magna-IR 550 spectrometer as a Nujol mull between KBr plates.…”
Section: Introductionmentioning
confidence: 99%